2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6748153
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollution effects on insulators of northern Egypt HV transmission lines

Abstract: Flashover of polluted high voltage insulators is a major problem for operation of power lines in Egypt. In 2010, insulators' pollution was the cause of several interruptions in the Egyptian electric network. Variations of climatic conditions and large industrial developments in the last few years call to update the pollution map of Egypt. To achieve this, six sites in northern Egypt with different types of pollution (industrial, desert, marine and their mixtures) have been investigated. To asses the pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Flashover depends on the type of pollution and time duration that the insulator is placed in the polluted environment [16]. Industrial, desert, and marine pollutions are the main three types of TL insulator pollution [17,18]. Industrial pollution is caused by industrial plants which produce pollutants such as chemical particles, dust, carbon, and cement and deposited on the insulator surface.…”
Section: High Voltage History and Main Aspectsmentioning
confidence: 99%
“…Flashover depends on the type of pollution and time duration that the insulator is placed in the polluted environment [16]. Industrial, desert, and marine pollutions are the main three types of TL insulator pollution [17,18]. Industrial pollution is caused by industrial plants which produce pollutants such as chemical particles, dust, carbon, and cement and deposited on the insulator surface.…”
Section: High Voltage History and Main Aspectsmentioning
confidence: 99%
“…Salt contamination and industrial pollution may cause flashovers and line outages, thereby affecting the power supply and reducing the reliability of the power system. To prevent insulator flashovers, maintenance staff need to periodically wash the insulators [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by J.Li [7] that this correlation can be used to determine the pollution severity and the flashover voltage occurrence. Other researcher used the 3rd, 5th, and 7th 𝐼 3 𝑟𝑑 (𝐼 5 𝑡ℎ + 𝐼 7 𝑇ℎ ) ⁄ to analyse the LC under different environmental condition where it has been reported that the 7th harmonic has a considerable effect on the performance of the LC under wetting conditions [8][9][10][11]. N.Bashir [12] used the third to fifth harmonic ratio of the LC to determine the effect of pollution severity on the aged glass insulator.…”
Section: Introductionmentioning
confidence: 99%